Pengaruh kecerdasan emosi dan kecerdasan spiritual ke atas salah laku remaja sekolah - Kamarudin, Norazwa Yeop (2013)
The objective of this research was to examine the influence of emotional intelligence and spiritual intelligence towards delinquency among adolescents in Johor Bahru District. This research involved the analyses to examine student’s level of both intelligences and involvement in the delinquent behaviors. This research also investigated on the influence of emotional intelligence and spiritual intelligence on adolescent delinquency and to examine the correlation between those intelligences. This quantitative research used survey method for the data collection. The data were analyzed using SPSS version 16.0 for correlation Pearson test, simple regression test and multiple regression test. A total of 370 respondents from five secondary schools in Johor Bahru district were involved in this study. Instrument used in this research was Sistem Salah Laku Displin Murid (SSDM) from Ministry of Education to measure delinquent behaviors among students. In order to measure emotional intelligence, Universiti Sains Malaysia Emotional Quotient Inventory (USMEQ-i) has been used while Malay Spiritual Well Being (Malay SWB) instrument was used to measure spiritual intelligence. The results showed that the level of emotional intelligence among the respondents was moderate while the level of spiritual intelligent among the respondents was high. The level of adolescent delinquency was lower. Analysis using Pearson correlation significant indicated that adolescent delinquency correlated significantly with spiritual intelligence but not with emotional intelligence. However analyses using multiple regression analysis, both intelligence significantly influence delinquency. Result also showed that emotional intelligence has moderate relationship with spiritual intelligence. This result can give input to the stakeholder to emphasize the spiritual and emotional intelligence elements in diminishing the involvement of adolescents in the delinquent behaviors.